2006
DOI: 10.1098/rstb.2006.1868
|View full text |Cite
|
Sign up to set email alerts
|

Darwin at the molecular scale: selection and variance in electron tunnelling proteins including cytochrome c oxidase

Abstract: Biological electron transfer is designed to connect catalytic clusters by chains of redox cofactors. A review of the characterized natural redox proteins with a critical eye for molecular scale measurement of variation and selection related to physiological function shows no statistically significant differences in the protein medium lying between cofactors engaged in physiologically beneficial or detrimental electron transfer. Instead, control of electron tunnelling over long distances relies overwhelmingly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
123
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(134 citation statements)
references
References 55 publications
10
123
0
1
Order By: Relevance
“…This result is in excellent agreement with the observed rate of 8 ϫ 10 8 s Ϫ1 . In the refined version, a of 0.82 was suggested for cytochrome c oxidase [instead of the generic value of 0.76 (14,42)]. With the observed rate constant, the value for would then become 0.72 eV, again in good agreement with the Moser-Dutton treatment.…”
Section: Resultssupporting
confidence: 58%
“…This result is in excellent agreement with the observed rate of 8 ϫ 10 8 s Ϫ1 . In the refined version, a of 0.82 was suggested for cytochrome c oxidase [instead of the generic value of 0.76 (14,42)]. With the observed rate constant, the value for would then become 0.72 eV, again in good agreement with the Moser-Dutton treatment.…”
Section: Resultssupporting
confidence: 58%
“…The heme iron separations differ in the two proteins by less than 0.5 Å, and the nearby methyl groups distances differ by 0.8 Å, based on the x-ray structures [differences well within the range of thermal fluctuations (19)]; the coupling pathway structure is nearly the same in the two proteins, involving the bonded His-Phe-His path linking irons and the direct methyl-tomethyl through-space contact. Taking a minimum donor-acceptor distance of 7.8 Å, a (generic) packing density value (2,14), and a typical ET reorganization energy (0.7 eV) places rates computed with packing analysis in agreement with experimental rates (20). However, recent studies have found a reorganization energy for cytochrome bo 3 of Ͻ0.2 eV, so the kinetics cannot be accommodated with the packing density reported by Dutton and coworkers (20).…”
Section: Coupling Routes and Tunneling Barriers In Cytochrome C Oxidasementioning
confidence: 70%
“…Taking a minimum donor-acceptor distance of 7.8 Å, a (generic) packing density value (2,14), and a typical ET reorganization energy (0.7 eV) places rates computed with packing analysis in agreement with experimental rates (20). However, recent studies have found a reorganization energy for cytochrome bo 3 of Ͻ0.2 eV, so the kinetics cannot be accommodated with the packing density reported by Dutton and coworkers (20).…”
Section: Coupling Routes and Tunneling Barriers In Cytochrome C Oxidasementioning
confidence: 70%
See 2 more Smart Citations